Guidelines for identifying risk vulnerabilities associated with ICT sourcing - A. Cachia; C. J. Kruger (South African Journal of Business Management, 2007)
As organizations broaden their organizational boundaries with sourcing practices, it is imperative to identify risk vulnerabilities from a wider perspective than before. Specifically, organizations that make substantial use of ICT suppliers need to understand the risk vulnerabilities associated with ICT sourcing partnerships. Unfortunately, due to vulnerabilities being addressed from different levels of erudition, an inclusive list of risk vulnerabilities, associated with ICT suppliers, does not exist within the ICT industry. This article not only address ICT risk management discrepancies and the importance of ICT supplier management, but in drawing on the collective knowledge contained in diverse sources, two distinct lists containing risk vulnerabilities, from the customer organization's perspective, are generated, all, in order to accelerate the understanding of exposure when dealing with ICT suppliers.
Keywords: 650